2018
DOI: 10.1371/journal.pone.0207440
|View full text |Cite
|
Sign up to set email alerts
|

Detection of central nervous system viral infections in adults in Manado, North Sulawesi, Indonesia

Abstract: Central nervous system (CNS) viral infections are important causes of morbidity and mortality worldwide but the systematic survey of patients admitted to hospitals with CNS infections in many countries, including Indonesia, is limited. To obtain more information regarding the causes of CNS infections in Indonesia, this study was performed to detect and identify viral agents associated with CNS infections amongst in-patients at a referral hospital in Manado, North Sulawesi, Indonesia. Adult patients admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 45 publications
3
21
0
10
Order By: Relevance
“…Overall, 5.8% (24/411, 95% CI 3.9À8.7%) of neonates were confirmed to have congenital CMV infection by pan-herpesvirus PCR and Sanger sequencing of PCR product in at least one type of specimen. No other pathogens were identified, although the panherpesvirus PCR can detect a broad range of herpesviruses including herpes simplex virus, Epstein-Barr virus, and varicellazoster virus (Anthony et al, 2015;Mawuntu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 5.8% (24/411, 95% CI 3.9À8.7%) of neonates were confirmed to have congenital CMV infection by pan-herpesvirus PCR and Sanger sequencing of PCR product in at least one type of specimen. No other pathogens were identified, although the panherpesvirus PCR can detect a broad range of herpesviruses including herpes simplex virus, Epstein-Barr virus, and varicellazoster virus (Anthony et al, 2015;Mawuntu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…All saliva and urine specimens were tested for the presence of CMV DNA by using pan-herpesvirus nested-PCR as described previously (Chmielewicz et al, 2001;Mawuntu et al, 2018). Briefly, total nucleic acids were extracted by using QIAamp MinElute Virus Spin Kit (Qiagen, Hilden, Germany) from 200 ml of specimens.…”
Section: Detection Of CMV Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,39,43,44 Globally, majority of studies have concluded that herpes simplex virus (HSV) is the most prevalent cause of VE. 4,12,25,43,[45][46][47][48][49][50][51][52][53][54][55][56] The pathogenic agents of VE vary from country to country. In Western countries such as France, England, and the United States, human simplex virus-1(HSV-1) has come up as the most prominent cause of sporadic VE.…”
Section: • Acute Ve • Postinfectious Encephalomyelitis • Slow Viral Imentioning
confidence: 99%
“…Thus, initial serological assays screening is recommended before sending the samples to higher laboratories. 56,122 Reverse Transcription PCR When ribonucleic acid (RNA) viruses have to be traced out, reverse transcription PCR comes into picture. It is similar to conventional PCR except for the first step where complimentary DNA (cDNA) is formulated out of RNA.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%